Anticipatory thinking and fiqh tawaqqu': the integration between the western and Islamic views - Abu Hassan, Muhammad Ikram; Kamarulzaman, Wirawani (Asian Scholar Network, 2023)
This paper explores anticipatory thinking from both Western and Islamic perspectives, with a particular focus on the concept of Fiqh Tawaqqu'. Anticipatory thinking involves the ability to proactively anticipate future challenges and opportunities, making it a crucial cognitive skill for individuals and teams. In the Western context, this paper discusses the elements of anticipatory thinking, including forecasting, scenario planning, risk assessment, opportunity recognition, and adaptability. It highlights the benefits of anticipatory thinking, such as improved decision-making, preparedness, and adaptability to change. In contrast, the paper delves into the Islamic perspective by defining Fiqh Tawaqqu' and its significance in Islamic jurisprudence (fiqh). Fiqh Tawaqqu' involves predicting the outcomes of actions based on evidence and experience, with a focus on achieving benefits (maslahah) for the ummah (community) and preventing harm (mafasid). The paper examines the acceptance and rejection of Fiqh Tawaqqu' among Muslim scholars, addressing the objections raised by some early Islamic figures. Furthermore, the paper offers examples of Fiqh Tawaqqu' that were initially met with skepticism but have proven to be relevant in contemporary contexts. It emphasizes the role of Fiqh Tawaqqu' in the development of jurisprudence and fatwa, enabling scholars to provide solutions to emerging societal issues. Finally, the paper explores the integration of anticipatory thinking and Fiqh Tawaqqu', highlighting the commonalities and potential synergies between these two approaches. It underscores the importance of forward-thinking and strategic planning in both Western and Islamic contexts to address complex challenges and shape a better future. This paper provides a comprehensive overview of anticipatory thinking and Fiqh Tawaqqu', fostering a deeper understanding of their relevance and implications in today's world.